A framework for physical education in the early years - Manners, H. (Falmer Press, 1995)
This best-selling book examines the Natioanl Curriculum Physical Education to Key Stage 1. It identifies six basic principles which provide the foundation for the rationale, curriculum content, the teaching and teh planning processes required.